Тhe solid phase interaction between platinum(II) and palladium(II) tetraammines with ammonium perrhenate in the air and inert atmosphere - V. I. Zarazhevskiy; V. V. Grebnev; E. V. Fesik; G. D. Mal’chikov (Тонкие химические технологии)
Тhe solid phase interaction in systems [Pt(NH3)4]Cl2 - NH4ReO4 and [Pd(NH3)4]Cl2 - NH4ReO4 in argon and on air was studied. The final products of the solid phase interaction of the specified mixtures are systems containing platinum or palladium and rhenium dioxide.